Coronary artery calcification in Korean patients with incident dialysis. Issue 3 (5th October 2016) - Bae, Eunjin; Seong, Eun Yong; Han, Byoung‐Geun; Kim, Dong Ki; Lim, Chun Soo; Kang, Shin‐Wook; Park, Cheol Whee; Kim, Chan‐Duck; Shin, Byung Chul; Kim, Sung Gyun; Chung, Wookyung; Park, Jae Yoon; et al.
Abstract: Introduction: Patients with chronic kidney disease have an extremely high risk of developing cardiovascular disease (CVD). In patients with end‐stage renal disease (ESRD), coronary artery calcification (CAC) is associated with increased mortality from CVD. Methods: The present study aimed to investigate the risk factors for CAC in Korean patients with incident dialysis. Data on 423 patients with ESRD who started dialysis therapy between December 2012 and March 2014 were obtained from 10 university‐affiliated hospitals. CAC was identified by using noncontrast‐enhanced cardiac multidetector computed tomography. The CAC score was calculated according to the Agatston score, with CAC‐positive subjects defined by an Agatston score >0. Findings: Patients' mean age was 55.6 ± 14.6 years, and 64.1% were men. The CAC‐positive rate was 63.8% (270 of 423). Results of univariate analyses showed significant differences in age, sex, etiology of ESRD and comorbid conditions according to the CAC score. However, results of multiple regression analysis showed that only a higher age was significantly associated with the CAC score. Receiver operating characteristic curves showed that the sensitivity and specificity of L‐spine radiography for diagnosing CAC were 56% and 91%, respectively, for diagnosing CAC (area under the curve, 0.735). Discussion: CAC was frequent in patients with incident dialysis, and multiple regression analysis showed that only age was significantly associated with the CAC score. In addition, L‐spine radiography could be a helpful modality for diagnosing CAC in patients with incident dialysis.